2016
DOI: 10.1007/s13105-016-0501-9
|View full text |Cite
|
Sign up to set email alerts
|

Vagotomy diminishes obesity in cafeteria rats by decreasing cholinergic potentiation of insulin release

Abstract: Herein, we investigated whether subdiaphragmatic vagotomy has benefits on obesity, body glucose homeostasis, and insulin secretion in cafeteria (CAF)-obese rats. Wistar rats were fed a standard or CAF diet for 12 weeks. Subsequently, CAF rats were randomly submitted to truncal vagotomy (CAF Vag) or sham operation (CAF Sham). CAF Sham rats were hyperphagic, obese, and presented metabolic disturbances, including hyperinsulinemia, glucose intolerance, insulin resistance, hyperglycemia, and hypertriglyceridemia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
6
17
0
5
Order By: Relevance
“…Previous studies showed that the pancreas is innervated by ‘sensory’ vagal fibers that may regulate insulin production through a sensory/efferent splanchnic network that involve other organs 2934 . These results concur with other studies showing that innervations of the adrenal glands modulate hyperglycemia in hemorrhagic shock 35,36 . Thus, we analyzed whether vagal stimulation attenuates hyperglycemia in adrenalectomized endotoxemic mice.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed that the pancreas is innervated by ‘sensory’ vagal fibers that may regulate insulin production through a sensory/efferent splanchnic network that involve other organs 2934 . These results concur with other studies showing that innervations of the adrenal glands modulate hyperglycemia in hemorrhagic shock 35,36 . Thus, we analyzed whether vagal stimulation attenuates hyperglycemia in adrenalectomized endotoxemic mice.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies also showed that the pancreas is innervated by ‘sensory’ vagal fibers from the hepatic subdiaphragmatic branches and suggest that the vagus nerve may regulate insulin production through a complex sensory/efferent splanchnic network that involves other organs 2934 . In agreement with these results, previous physiological studies showed that innervations of the adrenal glands modulate hyperglycemia in hemorrhagic shock 35,36 . Our current results show that efferent vagal stimulation induced insulin and adrenalectomy prevented vagal control of hyperglycemia in endotoxemia.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that vagotomy-induced reduction in insulin clearance is a phenomenon observed only in an obese mouse model, probably because they experienced malnutrition during early life. In fact, in nonprogramming obese rats, vagotomy also reduced insulin secretion but in contrast with our data, the insulinemia was reduced [ 24 ], which reinforces our idea that insulin clearance reduction induced by vagotomy may be dependent on metabolic programming. Although not evaluated, it seems that mice fed on a low-protein diet early in life followed by a regular diet in adulthood also develop decreased insulin clearance.…”
Section: Discussionsupporting
confidence: 89%
“…After 5 weeks, the Lee obesity index of rats in the HFD group was calculated by dividing the cube root of BW (g) by nasoanal length (cm) and multiplying the result by 1000, and rats with lee obesity index greater than 310 were considered obese (17,19). were separated from the esophagus and cut off (19,21). After the operation, rats were received systemic analgesic (Ibuprofen 5mg/kg SC) for 3 days in order to decrease postoperative pain (22) and subcutaneous 10 cm glucose 5% (Figure 1).…”
Section: Induction Of Experimental Hyperlipidemia In Ratsmentioning
confidence: 99%